2019
DOI: 10.1108/srj-03-2018-0078
|View full text |Cite
|
Sign up to set email alerts
|

CSR and sustainability reporting practices in India: an in-depth content analysis of top-listed companies

Abstract: Purpose The purpose of this paper is to comprehensively analyze the corporate social responsibility (CSR) and sustainability reporting (SR) practices of Indian companies in terms of disclosure quantity and quality, and to investigate the differences in SR practices by SR dimension, industry, ownership structure, firm size and profitability. Design/methodology/approach Data are collected from annual reports/business responsibility reports (BRR)/CSR/sustainability reports of 60 top-listed companies in India. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
108
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(119 citation statements)
references
References 30 publications
8
108
2
1
Order By: Relevance
“…The conducted research showed that the percentage of disclosures in CSR reporting in the economic, environmental, and social categories for the Petrol and Power industry was significantly higher than the percentage of disclosure for the other industries. These conclusions were consistent, e.g., with the research conducted by Aggarwal and Singh [38] in India; by Gamerschlag, Möller, and Verbeeten [46] in Germany; and Reverte [44] in Spain. The results were inconsistent with the research conducted by Branco and Rodrigues [4] in Portugal.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The conducted research showed that the percentage of disclosures in CSR reporting in the economic, environmental, and social categories for the Petrol and Power industry was significantly higher than the percentage of disclosure for the other industries. These conclusions were consistent, e.g., with the research conducted by Aggarwal and Singh [38] in India; by Gamerschlag, Möller, and Verbeeten [46] in Germany; and Reverte [44] in Spain. The results were inconsistent with the research conducted by Branco and Rodrigues [4] in Portugal.…”
Section: Discussionsupporting
confidence: 90%
“…The analysis also showed that the percentage of disclosures for companies from the Financial Services industry was significantly higher than for companies from the Consumer Goods industry. In previous research, companies from the Financial Services industry were often excluded from the sample [32,38,44,50] mainly because of the special accounting regulations applicable to them [44,50]. The results of our research in this area were inconsistent with Tagesson, Blank, Broberg, and Collin [37] and with the results of the research of Gamerschlag, Möller, and Verbeeten, [46].…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Public awareness of corporate environmental impacts has increased over the years [179,180], in turn increasing the expectations of society for enhanced corporate responsibility [181]. In addition, there have been regulatory changes such as those associated with the Companies Act 2013, as well changes in external certification and codes and guidelines [182,183], which encourage improvement in CED. Overall, when society's expectations are higher, it is anticipated that corporations increase disclosure in order to maintain legitimacy.…”
Section: Hypothesis 1 (H1)mentioning
confidence: 99%